Assessment of development results : evaluation of UNDP contribution : countries of the Organisation of Eastern Caribbean States & Barbados (UNDP New YorkUS, 2009)
Covers governance, poverty reduction, environment and disaster management/response as well as cross-cutting themes such as gender and HIV/AIDS
Keywords: DEVELOPMENT AID